Chemical Fluid Deposition of Hf-Zr-O-based Thin Films using Supercritical Carbon Dioxide Fluid. Issue 1729 (2015) - Shiokawa, Marina; Izaki, Katsushi; Funakubo, Hiroshi; Uchida, Hiroshi
ABSTRACT: We propose some chemical processing procedures for fabricating thin films in Hf-Zr-O system by a unique film deposition technique using supercritical carbon dioxide fluid (scCO2 ), i.e., supercritical fluid deposition (SCFD), which would be an prospective approach for fabricating metal-oxide films for integrated circuits because of its unique characteristics; e.g., extraction ability, transportation capability, and reaction equilibrium etc., are quite favorable for the film deposition from metal-complex precursors. The SCFD was accomplished in a closed batch-type reaction apparatus, consisting of two steps; (a) material deposition and (b) subsequent post-treatment under scCO2 atmosphere. Thin films of amorphous Hf-Zr-O were deposited on platinized silicon [(111)Pt/TiO2 /(100)Si] substrates by SCFD using metal-complex precursors M [OCH(CH3 )]2 (C9 H11 O2 )2 ( M = Hf or Zr) at reaction temperature of 100 – 300 °C, significantly lower than those for MOCVD. These films possessed dielectric permittivity's of approximately 20 – 25, comparable to those from conventional processes, although they still included residue of organic species that prompt the dielectric degradation under lower-frequency bias application.